A Youth Counter-Narrative on Trafficking and Smuggling from Africa to Europe. Issue 2 (3rd July 2017) - Tomei, Renato; Chetty, Rajendra
ABSTRACT: This article features the personal experiences of a young African woman victim of trafficking and smuggling from Nigeria to Italy. The aim of the article is to provide a counter-narrative on the phenomenon of human trafficking, by engaging with the youth's lived experiences. The story forms part of a wider database of youth counter-narratives, gathered by the authors in different parts of the world (Italy, South Africa, and Ethiopia). The narrative will be discussed on the basis of four identified elements, and the reflection addresses them within the wider context of trafficking, smuggling, and human migration. The conclusion drawn is that the language of youth counter-narratives can represent a useful tool to address the complexity of social issues, in particular when they refer to lived experiences of youngsters who have been subjected to different forms of oppression and violence. It also represents a sort of liberation from cultural homogenisation, forcing the readers to engage with a "new humanism."